Analysis of Cyber Infinity Game User Interface Design - Widayati, Yohana Tri; Prakoso, Satrio Agung; Widjaja, Stephanus; Wicaksono, Adityo Putro; Risti, Endah Ambar (Jurnal Transformatika, 2023)
The development of video games in Indonesia has grown rapidly since 2015, providing quite a large opportunity for the local game industry to compete in the video game market in Indonesia. Video games developed by local developers have not met players' expectations. Video game development needs to be done so that developers from abroad do not completely control the video game market in Indonesia. Game Cyber Infinity is one of the video games developed to answer the local market's needs. It was developed using the Design Thinking method with five stages: Empathize, Define, Ideate, Prototype, and Test. This research produced a Cyber Infinity game prototype with testing using the Black Box testing method.